2022
DOI: 10.3389/fbioe.2022.821428
|View full text |Cite
|
Sign up to set email alerts
|

Introgression of the Aedes aegypti Red-Eye Genetic Sexing Strains Into Different Genomic Backgrounds for Sterile Insect Technique Applications

Abstract: Aedes aegypti is an invasive mosquito species and major vector of human arboviruses. A wide variety of control methods have been employed to combat mosquito populations. One of them is the sterile insect technique (SIT) that has recently attracted considerable research efforts due to its proven record of success and the absence of harmful environmental footprints. The efficiency and cost-effectiveness of SIT is significantly enhanced by male-only releases. For mosquito SIT, male-only releases are ideally neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 71 publications
(93 reference statements)
1
8
0
Order By: Relevance
“…Indeed, releasing GSS males carrying the local genomic background will enhance the efficiency of SIT since their mating competitiveness is likely to be higher than that of males of different origin. In addition, the SIT application with local males is not expected to raise biosafety and biosecurity concerns compared to a trial which would be based on mosquitoes originated from a different geographical region ( Bouyer et al, 2020 ; WHO and IAEA, 2020 ; Augustinos et al, 2022 ). In the present study, the red eyes mutation and the inversion Inv35, which were used in the initial construction of the Ae.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, releasing GSS males carrying the local genomic background will enhance the efficiency of SIT since their mating competitiveness is likely to be higher than that of males of different origin. In addition, the SIT application with local males is not expected to raise biosafety and biosecurity concerns compared to a trial which would be based on mosquitoes originated from a different geographical region ( Bouyer et al, 2020 ; WHO and IAEA, 2020 ; Augustinos et al, 2022 ). In the present study, the red eyes mutation and the inversion Inv35, which were used in the initial construction of the Ae.…”
Section: Discussionmentioning
confidence: 99%
“…In our recently published studies, we reported the construction of the red-eye GSS ( Koskinioti et al, 2021 ) and the introduction of Inv35 to suppress recombination ( Augustinos et al, 2020 ). However, the recombination rate as well as the overall performance of a strain depends on several factors, including genomic background ( Ouda and Wood, 1985 ; Augustinos et al, 2020 , 2022 ; Carvalho et al, 2020 ). Therefore, in the present study, we introgressed the red eye mutation and the chromosomal inversion Inv35 in a wild population from Pakistan to assess the impact of the local genomic background on the genetic stability and the biological quality of newly constructed strains under laboratory rearing conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations